2015
DOI: 10.1016/j.pmedr.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sedentary behavior among children and adolescents living in an area affected by the 2011 Great East Japan earthquake and tsunami for 3years

Abstract: The purpose of this study is to examine the change in physical activity levels among children and adolescents living in the area affected by the 2011 earthquake and tsunami for 3 years immediately following the disaster. Children and adolescents graded four to nine and attending school in the Pacific coastal area of northern Japan were included in a total of four serial prevalence investigations: the first at 6 months after the earthquake/tsunami (I, n = 434) and additional surveys at 1 year (II, n = 437), 2 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
3
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 16 publications
(16 reference statements)
1
28
3
5
Order By: Relevance
“…Therefore, girls may be more sensitive to chronic stress than boys in such disasters. According to the results of the present study, there was no gender difference in COR, but our previous study reported that there was a gender difference in the physical activity level of disaster-afflicted children and adolescents, and the difference continued after the disaster 37) . Therefore, it is considered that the difference between physical activity level and chronic stress sensitivity caused a difference in SF, and a concomitant change in SIgA-C.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Therefore, girls may be more sensitive to chronic stress than boys in such disasters. According to the results of the present study, there was no gender difference in COR, but our previous study reported that there was a gender difference in the physical activity level of disaster-afflicted children and adolescents, and the difference continued after the disaster 37) . Therefore, it is considered that the difference between physical activity level and chronic stress sensitivity caused a difference in SF, and a concomitant change in SIgA-C.…”
Section: Discussioncontrasting
confidence: 47%
“…*p < 0.05, **p < 0.01, ***p < 0.001. a 4th to 6th grade elementary school students, b 7th to 9th grade junior high school students. school students and female students 37) . Accordingly, it is hard to say whether the life environment of the disaster area has fully recovered, even after 5 years; and it is speculated that junior high school students, who had mentally unstable periods of puberty during this time, had a greater accumulation of mental influence than elementary school students.…”
Section: Discussionmentioning
confidence: 99%
“…These are the very conditions that have also been associated with an increased risk of hospitalisation and death from COVID-19 [11]. Some evidence from other emergencies suggests that the deleterious effects of physical inactivity and sedentarism that begin during an outbreak may continue for some time after the end of the outbreak [12]. Conversely, this new reality may encourage more physical activity as people seek respite from being stuck at home, particularly if the reduction in traffic makes built environments more conducive to physical activity in public spaces.…”
Section: Impact Of Control Measures On Diet and Physical Activitymentioning
confidence: 99%
“…However, a previous study has assessed the impact of natural disasters on physical activity. After the devastating earthquake and tsunami in Japan in 2011, there was a significant decrease in physical activity detectable over the three years following the disaster [ 3 ].…”
mentioning
confidence: 99%
“…In the published literature, there is no existing data investigating changes in physical activity during pandemics. However, a previous study has shown a significant decrease in physical activity following the catastrophic earthquake and tsunami in Japan in 2011 [ 3 ].…”
mentioning
confidence: 99%